PERANCANGAN VIDEO STEREOSCOPIC 3D DENGAN 2 KAMERA SMARTPHONE MENGGUNAKAN METODE COLOR ANAGLYPH - Sucipto, Sucipto (Universitas Respati Yogyakarta, 2013)
3D Stereoscopy also called stereoscopic or 3D imaging refers to a technique for creating or enhancing the illusion of depth to the picture by presenting two offset images separately to the left and right eye of the viewer. Two-dimensional images are then combined in the brain to give the perception of 3D depth. One method to represent the level of depth with stereoscopic. Two stereoscopic images are stacked, there will be the so-called image disparity (disparity image) that is separate duplicate images because of the different parallax. Disparity image is created because of stereobase, ie the distance between the camera lens axis. The distance between the two cameras, can be analogous to the distance of the two eyes are large 65 mm. Factors that affect the stereoscopic video is video processing performed by optimization of standard anaglyph, with color correction and gamma level of the video, shooting technique and the distance between the object lens with the camera, it is supported by the change in value significantly between techniques establishing shot (ES), tracking shot (TS) and a panning shot (PS). tracking shot (TS). distance between an object lens with the camera also has an effect, on the first visible value of 75 lux at a distance object with camera lenses over 20 meters were taken using a technique establishing shot (ES) has a value score an average of 4.6 to 6.8 while tracking shot (TS) have the highest scores, with an average score of 6.6 to 9, while for objects recorded average value is the highest PK (Pusat Keramaian) object with an average score of 2.6 object followed by a PA (Pemandangan Alam) object with an average score of 2.4. Keyword : stereoscopic, disparity, parallax, stereobase, gamma.